An Integrated Sand Control Method Evaluation - Samsuri, Ariffin; Sim, S. H.; Tan, C. H. (2003)
A numerical model has been developed that is able to predict the onset of sand production and evaluate the performance of sand control, should sand production becomes unavoidable. The simulation of perforation stability was carried out first using a two-dimensional, two-phase finite-element model. This is a coupled geomechanical and fluid flow model. The rock was assumed to be heterogeneous and the pores were completely filled with fluid with fluid. The deformation condition is considered as plane strain and either the Mohr-Coulomb or Drucker-Prager yield surface was used to designate perforation failure. The model enables the study on the effect of perforation pattern and density on wellbore stability. Simulation runs on a sample model indicated that the lowest pore pressure, the greatest shear stress and minor principle stress were found close to the perforation tip. The greatest major principle stress occured around the center of perforation roof. In other words, the perforation was always surrounded by high stress concentration. In those events when sand production is a certainty, it is necessary to evaluate the performance of sand control methods to be used. A finite difference flow model was used to calculate the additional pressure drop from the well boundary to the sand control screen. The Forchheimer equation was used in place of the more conservative Darcy equation so that the effect of high-velocity flow to the well performance could be considered. The result of several sample runs indicated firm relationship between total additional pressure drop and the flow rate imposed, where a larger flow rate will cause greater pressure loss. Also, the well productivity showed improvement with more shots per foot. The result suggested that the majority of well pressure drop was caused by the casing-cement tunnel.